Meta-analysis of the effects of essential oils on ruminal fermentation and performance of sheep - Torres, R. N.S. [UNESP]; Moura, D. C.; Ghedini, C. P.; Ezequiel, J. M.B. [UNESP]; Almeida, M. T.C. (Elsevier, 2020)
This study was carried to evaluate the effects of essential oils (EO) supplementation to sheep diets on their performance and ruminal fermentation characteristics through meta-analysis. Twenty-one peer-reviewed publications with 50 treatment means were included in the data set. The effects of EO as an additive in sheep diets were evaluated using random-effect models to examine the raw mean difference (RMD) between EO treatment (diets with EO inclusion as an additive) and control treatment (diets with no additives). Heterogeneity was explored by meta-regression and subgroup analysis performed for: animal age; EO supplementation period, experimental design; EO extraction methods; amount of EO and primary bioactive compound in EO. The major bioactive compounds in EO were: carnosic acid (25.71%), carvacrol (22.86%) and thymol (11.42%). Essential oils supplementation reduced average daily gain (RMD = -0.01 kg/day; P < .0001), slaughter weight (RMD = -0.77 kg; P = 0.02) and hot carcass weight (RMD = -0.56 kg; P = 0.01). Similarly, crude protein digestibility, rumen protozoa population and acetate concentration were depressed in animals receiving EO supplementation. Improvements on neutral detergent fiber digestibility and rumen concentration of propionate and butyrate were reported with EO supplementation. Among the covariates, inclusion levels of EO greater than 100 mg/kg of DM reduced average daily gain, whereas, inclusion levels greater than 200 mg/kg of DM, negatively impacted slaughter weight. The best results regarding rumen propionate and NH3-N concentrations were reported when EO were fed for less than 30 days, suggesting that an adaptation to the antimicrobial activity of essential oils may occur with time. The results reported in our meta-analysis demonstrate no effectiveness of EO in improving sheep performance.
Keywords: carcass; lamb; Phytogenic additives; protozoa